Lithium aluminosilicate ESP cover plate glass and preparation process thereof

Through the preparation process of lithium aluminum silicate ESP cover glass, the problem of increased strength after chemical strengthening of glass but accompanied by explosion and surface defects is solved, and high flexural strength, microhardness and chemical corrosion resistance are achieved, satisfying the high-end Performance requirements for applications.

CN119241065APending Publication Date: 2025-01-03QINGDAO FUSION NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411163318.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The strength of existing glasses increases after chemical reinforcement, but with explosion and increased surface defects, and the mechanical properties of ultra-thin glasses decline, making it difficult to meet the needs of high-end applications.

Method used

The preparation process of lithium aluminum silicate ESP cover glass is adopted, and the original sheet glass material square and the molten salt material square for tempering are reasonably regulated, combined with the temperature system and time system, to form high strength, low thermal expansion coefficient and excellent appearance glass products.

Benefits of technology

The glass has high flexural strength, microhardness, chemical corrosion resistance and low thermal expansion coefficient, which enhances the surface compressive stress and stress layer depth of the glass, and improves the overall performance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses lithium aluminosilicate ESP cover plate glass and a preparation process thereof. The lithium aluminosilicate ESP cover plate glass is prepared from the following components in percentage by mass: 45 to 50 percent of SiO2, 15 to 18 percent of Al2O3, 3 to 5 percent of Li2CO3, 2 to 4 percent of Na2CO3, 1 to 3 percent of ZrSiO4, 9 to 11 percent of B2O3, 2 to 4 percent of K2CO3, 2 to 4 percent of MgO, 1 to 3 percent of Y2O3, 2 to 4 percent of KNO3, 5 to 8 percent of calcite, 1 to 3 percent of Na2SO4, 0.3 to 0.5 percent of C powder, 1 to 3 percent of ZrO2 and 0.5 to 1 percent of SnO2. According to the invention, the glass material and the molten salt material for tempering are regulated and controlled, and chemical tempering is carried out through a special process, so that the glass has excellent properties such as excellent appearance, high visible light transmittance, extremely few stripes, good chemical corrosion resistance, high breaking strength, high microhardness and relatively low thermal expansion coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to a lithium aluminum silicate ESP cover glass and a preparation process thereof. Background Art

[0002] In the absence of any defects, the theoretical strength of glass is very different from its actual strength, which seriously limits the application of glass in actual production and high-end fields. The depth of microcracks on the glass surface is 4-8nm, and every 1mm 2 There are about 300 microcracks on the surface of glass, and the thinner the glass is, the greater the impact of microcracks on its strength. In order to improve the strength of glass and overcome the generation of microcracks, it is necessary to develop a suitable glass material and preparation process.

[0003] With the development and growth of the touch screen market, the constant pursuit of thin cover glass has become a new trend in the cover glass industry, promoting the development of cover glass in a thinner direction. The sharp reduction in glass thickness makes thin glass have advantages such as small volume and light weight compared to ordinary glass, but it also significantly reduces the mechanical properties of glass. Therefore, research on ultra-thin glass strengthening is imperative.

[0004] Glass chemical strengthening technology refers to placing glass in molten salt at a specific temperature, exchanging the smaller ion radius on the glass surface with the larger ion radius in the molten salt, and achieving the purpose of improving the glass strength after a period of reaction. However, under glass chemical strengthening, the strength of the strengthened glass is greatly improved, but it is also accompanied by glass cracking and increased defects on the glass surface. Therefore, the selection and ratio of molten salt has also become a constraint on the development of glass chemical strengthening technology.

[0005] In summary, in order to address the above-mentioned problems, it is necessary to further develop suitable glass materials and glass chemical strengthening methods to improve glass performance. Summary of the invention

[0006] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a lithium aluminum silicate ESP cover glass and a preparation process thereof, and to reasonably control the original glass material formula and the appropriate molten salt material formula for tempering, and to make the original glass of the present invention chemically tempered by a special process through a temperature system, a time system, etc., so as to have excellent appearance, high visible light transmittance, very few stripes, good chemical corrosion resistance, high flexural strength, high microhardness, low thermal expansion coefficient and other excellent properties.

[0007] The technical solution of the present invention is: On the one hand, the present invention provides a lithium aluminum silicate ESP cover glass, comprising the following components in mass percentage: SiO2 45-50%, Al2O3 15-18%, Li2CO3 3-5%, Na2CO3 2-4%, ZrSiO4 1-3%, B2O3 9-11%, K2CO3 2-4%, MgO 2-4%, Y2O3 1-3%, KNO3 2-4%, calcite 5-8%, Na2SO4 1-3%, C powder 0.3-0.5%, ZrO2 1-3% and SnO2 0.5-1%.

[0008] Preferably, the following components are included in mass percentage: SiO2 46%, Al2O3 16%, Li2CO3 3.5%, Na2CO3 2.5%, ZrSiO4 2.5%, B2O3 10%, K2CO3 2.5%, MgO 3%, Y2O3 1.5%, KNO3 3%, calcite 5.5%, Na2SO4 1.5%, C powder 0.4%, ZrO2 1.5% and SnO2 0.6%.

[0009] The basic components of the glass of the present invention include raw materials such as alkali metal oxide R2O (mainly Na2O provided by Na2CO3, K2O provided by K2CO3 and KNO3, and Li2O provided by Li2CO3), SiO2, Al2O3 of analytical grade, and metal oxides (CaO and MgO provided by calcite).

[0010] The SiO2 structural unit is silicon oxygen tetrahedron [SiO4]. These [SiO4] are interconnected in the glass and extend infinitely to form a glass skeleton. The presence of SiO2 can improve the chemical stability of the glass, enhance the mechanical strength, and increase the hardness of the glass. However, too high a SiO2 content will cause the viscosity of the glass liquid to be too high, which is not conducive to the clarification and melting of the glass. Therefore, the mass fraction of SiO2 in the glass should be controlled at 45-50%.

[0011] Al2O3 exists in the glass in the form of aluminum oxide tetrahedron [AlO4] and aluminum oxide octahedron [AlO6]. Due to the influence of alkali metal oxide (R2O), when the molar ratio of R2O / Al2O3 is greater than 1, Al2O3 mainly exists in the form of aluminum oxide tetrahedron [AlO4]. 3+ As a network-forming ion; when the molar ratio of R2O / Al2O3 is less than 1, Al2O3 mainly coexists in the form of aluminum oxide tetrahedron [AlO4] and aluminum oxide octahedron [AlO6], and Al 3+As a network binder, adding an appropriate amount of Al2O3 to the glass components can effectively improve the stability of the glass at high temperatures, improve the chemical stability of the glass, reduce the tendency of crystallization, and enhance the mechanical properties of the glass. However, the melting point of Al2O3 is very high (above 2000℃). Limited by the current industrial melting capacity and conditions, the content of Al2O3 should be controlled below 20wt.%.

[0012] The thermal expansion coefficient of glass mainly depends on the attraction between cations and anions, and is also affected by the density of the glass network. When the Al2O3 / SiO2 mass ratio is greater than 0.3, under the condition of sufficient free oxygen, the hexacoordinated Al2O3 can be transformed into a tetracoordinated one and enter the network, repairing the broken network and reducing the thermal expansion coefficient of the glass.

[0013] Alkali metal oxide R2O is the most important network exosome oxide and the core component that enables glass to be chemically strengthened through ion exchange. In glass production, alkali metal oxide R2O mainly includes Na2O, K2O, and Li2O, and is the main component that reduces the melting temperature of glass. However, excessive R2O will significantly reduce the water resistance of glass and reduce the surface compressive stress during chemical strengthening. In addition, alkali metal oxides exist in the network gap in the form of network exosomes. If the total content of alkali metals remains unchanged, changing the ratio of any two of them will produce a mixed alkali effect, which enhances the mechanical properties of the glass. Moreover, the presence of Na2O and Li2O at the same time can perform two-step ion exchange on glass to obtain glass products with better impact resistance.

[0014] Li2O, Na2O, and K2O are the main components for reducing the melting temperature of glass. Moreover, Li2O can react with SiO2 at a relatively low temperature to generate silicate substances, and can act as a strong co-solvent in the glass composition. However, excessive R2O will reduce the water resistance of the glass and reduce the surface compressive stress during chemical strengthening of the glass. Therefore, the R2O content should be controlled within a certain range. In order to ensure good chemical strengthening effect of the present invention and smooth ion exchange, the material formula must contain Na2O and Li2O at the same time. The glass can be subjected to two-step ion exchange to obtain glass with high strength, high hardness, and high impact resistance.

[0015] Alkaline earth metal oxides RO (including CaO and MgO) can promote glass melting, but if the RO content is too high, the material properties of the glass will be shortened and the risk of crystallization will occur easily; alkaline earth metal oxide CaO is not conducive to ion exchange and is the culprit of "poisoning" of chemically strengthened molten salts; MgO can enhance the chemical stability of glass and optimize the mechanical properties, and MgO has a certain fluxing effect at high temperatures, but excessive MgO will promote glass crystallization and increase the difficulty of controlling molding, so the MgO content is often lower than 12wt.%.

[0016] The introduction of SnO2 will not cause changes in melting and molding conditions, and plays an important role in the stability of float glass process molding. SnO2 is a high-quality transparent conductive material that can significantly improve the chemical stability of glass and at the same time improve the transmittance of glass.

[0017] Y2O3 doping can change the [SiO4] tetrahedral structural unit in lithium aluminum silicate glass, increase the number of non-bridging oxygen and bridging oxygen, and reduce the number of connections of each tetrahedron, thus changing the processing properties of the glass. 2 、5P 6 Due to the shielding effect of the orbit, it combines well with the atomic nucleus, making its absorption peak for visible light sharp and almost unaffected by the outside world, making the glass transparent, with high visible light transmittance and excellent appearance.

[0018] ZrO2 is a material with excellent properties, such as wear resistance, heat resistance, corrosion resistance and oxidation resistance. ZrO2 can act as a network former, which can significantly improve the strength and thermal stability of glass, and can significantly improve the alkali corrosion resistance of the glass matrix. Zirconium ions exist in the form of [ZrO6] octahedrons in glass. The Zr-O-Si bond strength is relatively high and difficult to be broken. At the same time, it can improve the fracture characteristics of glass and reduce the risk of glass fracture. However, ZrO2 is a refractory oxide. If excessive ZrO2 is introduced, it will cause melting problems and potential crystallization tendency, and will also have a negative effect on the performance of the glass.

[0019] On the other hand, the present invention provides a preparation process of the lithium aluminum silicate ESP cover glass, wherein the components are uniformly mixed into a batch material, kept at 1400-1450° C. for 10-20 min, then heated to 1500-1600° C. at a heating rate of 2° C. / min, kept for 2-2.5 h for clarification and homogenization; then annealed at 580-680° C. for 2-3 h, then cooled to room temperature, cut, polished, processed into glass sheets, and finally glass strengthened.

[0020] Chemical strengthening and physical tempering (also known as thermal tempering) are commonly used glass strengthening methods for ESP raw glass. Chemical strengthening, also known as ion exchange, is a glass strengthening method that creates surface compressive stress (CS) through the crowding effect (introducing large-radius ions from the outside to replace small-radius ions in the glass network), thereby increasing load resistance.

[0021] Chemical strengthening of glass is to strengthen glass by ion exchange, also known as ion exchange strengthening method, which is widely used because it can introduce compressive stress on the glass surface to improve the mechanical strength of glass. According to the temperature of ion exchange and the type of ion exchange, it can be divided into high temperature ion exchange method and low temperature ion exchange method.

[0022] The ion exchange temperature of high-temperature ion strengthening is higher than Tg. It mainly forms a compressive stress layer of a certain depth on the glass surface by precipitating microcrystals with a low thermal expansion coefficient on the glass surface. However, the strengthened glass is easy to deform, the process is difficult to control, and large-scale production is difficult. Low-temperature ion strengthening mainly forms a compressive stress layer by exchanging small-radius alkali metal ions on the glass surface with large-radius alkali metal ions in the molten salt. Glass strengthened by low-temperature ions is not easy to deform, and the ion exchange process parameters are easy to control.

[0023] The lithium aluminum silicate ESP cover glass of the present invention has a very excellent ion exchange capacity compared with the traditional soda-lime silicate glass. The mass fraction of Al2O3 in the glass frit of the present invention is above 15%, and there are a large number of [AlO4] tetrahedrons and [SiO4] tetrahedrons in the glass, which together constitute the skeleton of the glass. The volume of [AlO4] (41cm 3 / mol) is larger than the volume of [SiO4] (27.24 cm 3 / mol); and the glass of the present invention contains Li + 、Na + The two alkali metal ions that can participate in ion exchange greatly improve the ion exchange rate and are more suitable for chemical enhancement treatment, thereby obtaining higher surface compressive stress and deeper stress layer depth.

[0024] Low temperature ion strengthening is divided into one-step low temperature ion strengthening and two-step low temperature ion strengthening. One-step low temperature ion strengthening is to use K with a slightly larger ion radius in the temperature region where the glass strain point is low. + With the surface Na + Exchange so that K + Enter the surface layer. This process is simple to handle and does not damage the transparency of the glass surface. The two-step low-temperature ion strengthening is divided into two steps for strengthening. By controlling the ion exchange temperature, exchange time, and molten salt composition of the two steps respectively, the depth and strength of the compressive stress layer finally formed on the glass are affected. Compared with the one-step method, it provides a more advanced performance improvement, especially in improving the mechanical properties of the glass.

[0025] The present invention selects a two-step low-temperature ion exchange method to strengthen the glass, and optimizes the strengthening temperature, strengthening time and molten salt formula to obtain the best strengthening effect.

[0026] Preferably, glass strengthening comprises the following steps: S1 first stage strengthening: put the glass into the preheating furnace and start preheating from room temperature, the preheating temperature is 350-380℃, the heating rate is 10-15℃ / min, and after reaching the preheating temperature, keep it warm for 10-15min; after preheating, continue to heat to 400-430℃ to strengthen the original glass, the strengthening time is 190-260min, and the strengthening and heat preservation time is 5-8min; then put the glass into 400-430℃ molten mixed molten salt for ion exchange, the time is 190-260min; then lift the glass to the top of the tempering furnace, take it out to cool, and drip salt for 10-20min, so that the molten salt on the glass drips into the tempering furnace; S2 two-stage strengthening: put the clean glass dripped with molten salt into the preheating furnace and start preheating from room temperature. The preheating temperature is 300-320℃, the heating rate is 10-15℃ / min, and it is kept warm for 10-15min after reaching the preheating temperature; after the preheating is completed, continue to heat to 350-380℃ to strengthen the original glass, the strengthening time is 150-180min, and the strengthening and heat preservation time is 10-15min; while keeping warm, perform the second salt dripping operation: the glass after strengthening and heat preservation for 10-20min is immersed in 350-380℃ molten mixed molten salt for secondary ion exchange for 150-180min; then lift the glass above the tempering furnace, drip salt for 20-30min, so that the molten salt on the glass drips into the tempering furnace; S3 annealing: after strengthening, the temperature is lowered to 320-350°C for annealing for 150-170 minutes, and then the temperature is further lowered to 10-30°C. After annealing, the lithium aluminum silicate ESP cover glass is obtained.

[0027] Preferably, in step S1, before preheating, the glass is first cleaned with deionized water and then dried, and the dried glass is wiped with alcohol gauze and then preheated again.

[0028] Preferably, in step S1, the molten mixed molten salt comprises the following components in mass percentage: KNO3 85-92%, NaNO3 4-9% and KCl 3-6%.

[0029] Preferably, in step S1, the molten mixed molten salt comprises the following components in percentage by mass: KNO3 88%, NaNO38% and KCl 4%.

[0030] Preferably, in step S2, the molten mixed salt includes the following components in mass percentage: KNO3 90-95%, KOH 1-4%, AgNO3 0.5-2.5%, CsNO3 0.5-2%, Al2O3 1-3%, and Na3PO4 0.5-1%.

[0031] Preferably, in step S2, the molten mixed salt includes the following components in mass percentage: KNO3 90%, KOH 4%, AgNO3 2.5%, CsNO3 1.5%, Al2O3 1.5%, and Na3PO4 0.5%.

[0032] The potassium ions in the KNO3 molten salt exchange with the sodium ions in the glass, which can form compressive stress on the glass surface and effectively improve the strength of the glass. At the same time, it can improve the impact resistance and wear resistance of the glass, and at the same time improve the flatness and light transmittance of the glass surface.

[0033] The KOH added to the molten salt is highly corrosive and can remove the hydroxyl layer on the glass surface, breaking the silicon-oxygen network. - 、F - and Cl - The polarity is large, and it is easy to react with Na in the glass + Affinity, accelerate Na + Migrate outward and significantly increase the ion exchange rate. The mechanism of action is mainly to chemically corrode the glass surface, destroy the spatial network structure of the glass, thereby increasing the ion exchange channel and making the ion exchange more agile. At the same time, corroding the glass surface can also eliminate the micro-crack layer on the glass surface, greatly improving the strength of the ion exchange glass.

[0034] AgNO3 added to molten salt can provide Ag + , which can enhance the optical properties of other ions in the glass. The incorporation of AgNO3 can cause the narrow area of ​​the glass interface to precipitate with a large density, resulting in crack deflection and crack bridging, thereby improving the flexural strength and microhardness of the glass.

[0035] CsNO3, together with KNO3, forms microcrack extensions on the glass surface through a chemical reaction and an ion exchange process, thereby increasing the flexural strength and microhardness of the glass. In the process of glass tempering molten salt, Al2O3 3+ Can replace part of Si 4+ , Al2O3 released during the tempering process 3+ It can affect the network structure of glass, thereby improving the flexural strength of glass. At the same time, the addition of Al2O3 will cause the internal structure of the glass to form a part of [AlO4], a small part of [AlO5], and [AlO6] during the strengthening process. These structural changes help to improve the thermal stability of glass, thereby reducing the thermal expansion coefficient of glass.

[0036] Na3PO4 can complex metal ions and enhance the strength between ions. Na3PO4 can react with Li2CO3 in the glass component of the original glass. + Reaction: 3Li ++Na3PO4=Li3PO4+3Na + The melting point of Li3PO4 is 837.5℃, which can remove the excess Li + It will precipitate, and KNO3 will react with it to purify the impurities in the molten salt, thereby improving the purity and transparency of the molten salt. It can also ensure that the size and stress value of the glass during the strengthening process are in a stable range, greatly improving the strengthening quality of glass products.

[0037] As a molten salt additive and co-solvent, KCl helps to lower the melting point of glass and promote uniform mixing of glass components. In the chemical strengthening process, it can achieve ion strengthening and hardening of glass at a lower temperature, improve the flexural strength and hardness of glass, and significantly increase the depth of exchange layer (DOL) of glass.

[0038] Compared with the prior art, the present invention has the following beneficial effects: The present invention reasonably regulates the original glass material and the appropriate tempering molten salt material, and chemically tempers the original glass of the present invention through a special process through a temperature system, a time system, etc., so that the original glass has excellent appearance, high visible light transmittance, very few stripes, good chemical corrosion resistance and other excellent properties. The original glass and the appropriate tempering molten salt, temperature system, time system, etc. are chemically tempered through a special process, so that the tempered glass has high flexural strength, high microhardness, low thermal expansion coefficient, enhanced surface compressive stress of the glass, stress layer depth, higher impact resistance and other good properties. DETAILED DESCRIPTION

[0039] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0040] Examples 1-5 and Comparative Examples 1-3 The 0.7 mm thick lithium aluminum silicate ESP cover glass material of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1-2: Table 1 Glass frits of Examples 1-5

[0041] Table 2 Glass frits of Comparative Examples 1-3

[0042] The preparation process of the lithium aluminum silicate ESP cover glass of Examples 1-5 and Comparative Examples 1-3 is as follows: the components are uniformly mixed into a batch material, and after being kept at 1400-1450° C. for 10-20 min, the temperature is increased to 1500-1600° C. at a heating rate of 2° C. / min, and the temperature is kept for 2-2.5 h for clarification and homogenization; then, annealing is performed at 580-680° C. for 2-3 h, and then cooled to room temperature, and then cut, polished, and processed into glass sheets, and finally glass strengthening is performed.

[0043] Specifically, glass strengthening includes the following steps: S1 first stage strengthening: first put the glass into the rack, put it in the ultrasonic cleaning machine for cleaning, the ultrasonic cleaning machine contains deionized water, then take out the rack with the glass, and put it into the oven for drying; wipe the dried glass with alcohol gauze once, and put it in the rack again, then put the clean glass and the rack into the preheating furnace, start preheating from room temperature, the preheating temperature is 350-380℃, the heating rate is 10-15℃ / min, and keep warm for 10-15min after reaching the preheating temperature; after the preheating is completed, continue to heat to 400-430℃ for strengthening the original glass, the strengthening time is 190-260min, and the strengthening and heat preservation time is 5-8min; then put the glass into the molten mixed molten salt at 400-430℃ for ion exchange, the time is 190-260min; then slowly lift the glass to the top of the tempering furnace, take it out for cooling, drip salt for 10-20min, so that the molten salt on the glass slowly drips into the tempering furnace; S2 two-stage strengthening: put the clean glass dripped with molten salt into the preheating furnace and start preheating from room temperature. The preheating temperature is 300-320℃, the heating rate is 10-15℃ / min, and it is kept warm for 10-15min after reaching the preheating temperature; after the preheating is completed, continue to heat to 350-380℃ to strengthen the original glass, the strengthening time is 150-180min, and the strengthening and heat preservation time is 10-15min; while keeping warm, perform the second salt dripping operation: after strengthening and heat preservation for 10-20min, the glass is immersed in 350-380℃ molten mixed molten salt for secondary ion exchange for 150-180min; then slowly lift the glass to the top of the tempering furnace, drip salt for 20-30min, so that the molten salt on the glass slowly drips into the tempering furnace; S3 annealing: after strengthening, the temperature is lowered to 320-350°C for annealing for 150-170 minutes, and then the temperature is further lowered to 10-30°C. After annealing, the lithium aluminum silicate ESP cover glass is obtained.

[0044] The parameter settings of each process in Examples 1-5 are shown in Table 3: Table 3 Parameter settings for each process in Examples 1-5

[0045] The parameter settings of each process in Comparative Examples 1-3 are the same as those in Example 1.

[0046] The molten mixed molten salt material for twice strengthening in Examples 1-5 is shown in Table 4: Table 4 The molten mixed molten salt material formula for double strengthening in Examples 1-5

[0047] Among them, the molten mixed molten salt material for double strengthening in Comparative Examples 1-3 is the same as that in Example 1.

[0048] The method for determining the density of the glass prepared in Examples 1-5 and Comparative Examples 1-3 is as follows: the density of the glass sample is measured using the Archimedean principle, the medium liquid is distilled water, and the mass of the sample is measured using a DE-120 high-density multifunctional electronic hydrometer. A small glass sample without defects such as bubbles and streaks is selected, and the sample is cleaned and dried with anhydrous ethanol; first weigh the mass of the sample in the air, click enter, the instrument automatically records the data and proceeds to the next step; then measure the mass of the sample in distilled water, click enter; the reading displayed by the instrument is the density of the measured sample. The glass density calculation formula is as follows: ρ=ρ0m2 / (m2-m1) Where: ρ-glass density, g / cm 3 ; m1-mass of sample in air, g; m2-mass of sample in distilled water, g; ρ0-density of air, g / cm 3 .

[0049] The method for measuring the flatness (before tempering) of the glass prepared in Examples 1-5 and Comparative Examples 1-3 is as follows: remove dust, foreign matter, etc. on the marble platform to keep the work surface clean so as not to affect the measurement results; take one piece of left, middle and right glass, mark the position of each edge of the sample (left, right, front and back) with a marker, transfer the sample to the marble platform (non-tin side facing up) according to "1100mm×1300mm", move the sample back and forth on the platform 3-5 times by hand, exhaust the air between the glass sample and the platform, and keep the edge of the sample about 50mm away from the edge of the marble platform during measurement; use a feeler gauge to measure once every approximately 100mm, and test the four edges of the sample in turn, take the maximum value measured on each edge as the flatness value of the edge, and keep a record.

[0050] The method for measuring the glass streaks prepared in Examples 1-5 and Comparative Examples 1-3 is as follows: fix the glass sample on the sample holder of the point light source detector (the pulling direction is perpendicular to the horizontal direction), observe the streak image displayed on the white screen by the light source passing through the glass sample, compare the most serious streaks with the streak standard, mark the streaks with a marker (marked with "×"), and measure the lateral position of the streaks on the glass ribbon with a tape measure (the left and right cutting edges of the center dividing plate are used as references).

[0051] The visible light transmittance of the glass prepared in Examples 1-5 and Comparative Examples 1-3 was measured by using a Shimadzu UV-2600i ultraviolet-visible spectrophotometer to measure the visible light transmittance of a 40 mm×20 mm×0.25 mm glass at a wavelength of 510 mm.

[0052] The chemical stability of the glass prepared in Examples 1-5 and Comparative Examples 1-3 is determined by: using a room temperature solution immersion method to determine the chemical stability of the sample, the solutions are distilled water, 1% H2SO4 solution, and 1% NaOH solution. The original glass sample is cut into a size of 4×4×10mm, placed in a beaker filled with a specified solution, and immersed for 480 hours. The corrosion resistance calculation formula is as follows: C=100(G1-G2) / S, mg / 100cm 2 Where: G1-weight of sample before immersion, mg; G2-weight of sample after immersion, mg; S-surface area of ​​sample before immersion, cm 2 .

[0053] The performance test results of the 0.7 mm thick lithium aluminum silicate ESP cover glass prepared in Examples 1-5 and Comparative Examples 1-3 are shown in Tables 5-6.

[0054] Table 5 Performance test results of lithium aluminosilicate ESP cover glass prepared in Examples 1-5

[0055] Table 6 Performance test results of lithium aluminum silicate ESP cover glass prepared in Comparative Examples 1-3

[0056] From the comparison of the data in Tables 5-6, it can be seen that the chemical stability of the glass prepared in Comparative Example 1 is significantly reduced compared with Example 1. This is because zirconium ions exist in the form of [ZrO6] octahedrons in the glass, and the Zr-O-Si bond strength is relatively high and difficult to be destroyed; ZrO2 can act as a network former, which can significantly improve the strength and thermal stability, and can significantly improve the alkali corrosion resistance of the glass matrix.

[0057] It can also be seen that the chemical stability of the glass prepared in Comparative Example 2 is reduced and the visible light transmittance is reduced compared with Example 2. This is because SnO2 can significantly improve the heat resistance and corrosion resistance of the glass, reduce the glass stress caused by temperature difference, and help improve the chemical stability of the glass.

[0058] In addition, compared with Example 3, the visible light transmittance of the glass prepared in Comparative Example 3 is reduced, and the number of glass stripes is increased. This is because Y2O3 is a rare earth element, the 4f orbital is not full, and is affected by the 5S 2 、5P 6 The shielding effect of the orbit makes it better combined with the atomic nucleus, making its absorption peak for visible light sharp, making the glass transparent and having a high visible light transmittance.

[0059] It can be seen from the above experiments that in glass production, the design of the material square has an important influence on the comprehensive performance of the glass. The present invention adds Li2CO3, Y2O3, ZrO2, SnO2 and the like to the glass raw materials, and the 0.7 mm thick lithium aluminum silicate ESP cover glass prepared by the float process has excellent appearance, high visible light transmittance, very few stripes, good chemical corrosion resistance and other excellent properties, and has good application prospects.

[0060] Comparative Examples 4-8 The difference between Comparative Example 4-8 and Examples 1-5 is that the molten mixed molten salt material for twice strengthening in Comparative Example 4-8 is shown in Table 7: Table 7 The molten mixed molten salt material formula for double strengthening in Comparative Examples 4-8

[0061] The method for determining the flexural strength of the glass prepared in Examples 1-5 and Comparative Examples 4-8 is as follows: a universal material testing machine produced by Changchun Kexin Testing Instrument Co., Ltd. is used to perform a three-point bending test on the glass, with a load of 0.5N applied, and the test results are averaged three times. The calculation formula for the flexural strength is as follows: σ = (3F × L) / (2b × h × h) Where: σ-bending strength, MPa; F-maximum load applied by the test bench when the sample breaks, N; L-span of the sample table, mm; b-width of the sample to be tested, mm; h-thickness of the sample to be tested, mm.

[0062] The method for determining the thermal expansion coefficient of the glass prepared in Examples 1-5 and Comparative Examples 4-8 is as follows: the strengthened glass is processed into a glass sample of 20×4×4 mm, the glass sample is placed in a thermal expansion instrument and uniformly heated (5°C / min), the length of the sample is observed to elongate as the temperature rises uniformly, and the elongation of the sample when the sample is heated from room temperature to 300°C is measured, thereby obtaining the thermal expansion coefficient of the glass. The expansion coefficient calculation formula is as follows: ɑ=

[0063] Where: ɑ-average linear expansion coefficient of the sample within the range of T1-T2, ℃ -1 ; L0-initial length of the sample, mm; L2, L1-length difference of the sample at temperature T2 and T1, mm; -Linear expansion coefficient of quartz glass = 5.98×10 -7 ℃ -1 (0-400℃).

[0064] The method for measuring the surface compressive stress and stress layer depth of the glass prepared in Examples 1-5 and Comparative Examples 4-8 is as follows: using the birefringence phenomenon generated when light propagates in an inhomogeneous medium, the surface stress meter can measure the surface compressive stress and stress layer depth of chemically tempered glass. This experiment uses a fully automatic surface stress tester FSM-6000 made in Japan to test the surface compressive stress CS and ion exchange layer depth DOL of the glass.

[0065] The method for measuring the microhardness of the glass prepared in Examples 1-5 and Comparative Examples 1-3 is as follows: a Vickers microhardness tester is used, the diamond indenter used is in the shape of a regular tetrahedron, the angle between the two opposite sides of the regular tetrahedron is 2α=136°, a constant load is applied to the glass surface, the area of ​​the indentation on the glass surface is tested, and the Vickers microhardness can be obtained by dividing the load by the indentation area. The constant load used in this experiment is 2.9415 N, the load duration is 15s, and the average value is taken from multiple tests. The calculation formula for Vickers microhardness is as follows: HV=0.102×

[0066] Where: HV - Vickers microhardness, kg / mm 2 ; P-load applied, N; α-angle between two opposite faces of regular tetrahedron, °; l - Average diagonal length of the indentation, mm.

[0067] The performance test results of the 0.7 mm thick lithium aluminum silicate ESP cover glass prepared in Examples 1-5 and Comparative Examples 4-8 are shown in Tables 8-9 Table 8 Performance test results of lithium aluminosilicate ESP cover glass prepared in Examples 1-5

[0068] Table 9 Performance test results of lithium aluminum silicate ESP cover glass prepared in Comparative Examples 4-8

[0069] From the comparison of the data in Tables 8-9, it can be seen that the flexural strength of the glass prepared in Comparative Example 4 is significantly reduced compared with Example 1. This is because the incorporation of AgNO3 can cause the narrow area of ​​the glass interface to precipitate with a large amount of density, resulting in crack deflection and crack bridging, thereby improving the flexural strength of the glass.

[0070] It can also be seen that the flexural strength and Vickers microhardness of the glass prepared in Comparative Example 5 are lower than those in Example 2. This is because CsNO3 and KNO3, together, form microcracks on the glass surface through a chemical reaction and an ion exchange process, thereby improving the flexural strength and Vickers microhardness of the glass. In addition, compared with Example 3, the thermal expansion coefficient of the glass prepared in Comparative Example 6 is significantly increased. This is because the addition of Al2O3 will cause the internal structure of the glass to form a portion of [AlO4], a small portion of [AlO5], and [AlO6] during the strengthening process. These structural changes help to improve the thermal stability of the glass, thereby reducing the thermal expansion coefficient of the glass.

[0071] Compared with Example 4, the surface compressive stress of the glass prepared in Comparative Example 7 is significantly reduced. This is mainly because the reaction of Na3PO4 and KNO3 can ensure that the external dimensions and stress values ​​of the glass are in a stable range during the strengthening process, thereby increasing the surface compressive stress of the glass.

[0072] Compared with Example 5, the flexural strength, Vickers microhardness, and stress layer depth of the glass prepared in Comparative Example 8 are significantly reduced. This is mainly because KCl can achieve ion strengthening and hardening of the glass at a lower temperature during the chemical strengthening process, improve the flexural strength and hardness of the glass, and significantly increase the exchange layer depth (DOL) of the glass.

[0073] Through the above experiments, it can be seen that in glass production, the design of materials and processes has an important influence on the comprehensive performance of glass. By reasonably regulating the raw glass materials and the appropriate molten salt materials for tempering, and through the temperature system, time system, etc., the raw glass of the present invention is chemically tempered by a special process, so that the raw glass has excellent appearance, high visible light transmittance, very few stripes, good chemical corrosion resistance and other excellent properties. After the raw glass and the appropriate molten salt for tempering, temperature system, time system, etc. are chemically tempered by a special process, the tempered glass has high flexural strength, high microhardness, low thermal expansion coefficient, enhanced surface compressive stress and stress layer depth of the glass, and has higher impact resistance and other good properties.

Claims

1. Lithium aluminum silicate ESP cover glass, characterized in that: It includes the following components in mass percentage: SiO2 45-50%, Al2O3 15-18%, Li2CO3 3-5%, Na2CO3 2-4%, ZrSiO4 1-3%, B2O3 9-11%, K2CO3 2-4%, MgO 2-4%, Y2O3 1-3%, KNO3 2-4%, calcite 5-8%, Na2SO4 1-3%, C powder 0.3-0.5%, ZrO2 1-3% and SnO2 0.5-1%.

2. The lithium aluminosilicate ESP cover glass according to claim 1, characterized in that: It includes the following components in mass percentage: SiO2 46%, Al2O3 16%, Li2CO3 3.5%, Na2CO3 2.5%, ZrSiO4 2.5%, B2O3 10%, K2CO3 2.5%, MgO 3%, Y2O3 1.5%, KNO3 3%, calcite 5.5%, Na2SO4 1.5%, C powder 0.4%, ZrO2 1.5% and SnO2 0.6%.

3. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 1, characterized in that: The components are uniformly mixed into a batch material, kept at 1400-1450℃ for 10-20min, then heated to 1500-1600℃ at a heating rate of 2℃ / min, and kept for 2-2.5h for clarification and homogenization; then annealed at 580-680℃ for 2-3h, then cooled to room temperature, cut, polished, processed into glass sheets, and finally glass strengthened.

4. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 3, characterized in that: Glass strengthening involves the following steps: S1 first stage strengthening: put the glass into the preheating furnace and start preheating from room temperature, the preheating temperature is 350-380℃, the heating rate is 10-15℃ / min, and after reaching the preheating temperature, keep it warm for 10-15min; after preheating, continue to heat to 400-430℃ to strengthen the original glass, the strengthening time is 190-260min, and the strengthening and heat preservation time is 5-8min; then put the glass into 400-430℃ molten mixed molten salt for ion exchange, the time is 190-260min; then lift the glass to the top of the tempering furnace, take it out to cool, and drip salt for 10-20min, so that the molten salt on the glass drips into the tempering furnace; S2 two-stage strengthening: put the clean glass dripped with molten salt into the preheating furnace and start preheating from room temperature. The preheating temperature is 300-320℃, the heating rate is 10-15℃ / min, and it is kept warm for 10-15min after reaching the preheating temperature; after the preheating is completed, continue to heat to 350-380℃ to strengthen the original glass, the strengthening time is 150-180min, and the strengthening and heat preservation time is 10-15min; while keeping warm, perform the second salt dripping operation: after strengthening and heat preservation for 10-20min, the glass is immersed in 350-380℃ molten mixed molten salt for secondary ion exchange for 150-180min; then lift the glass above the tempering furnace, drip salt for 20-30min, so that the molten salt on the glass drips into the tempering furnace; S3 annealing: after strengthening, the temperature is lowered to 320-350°C for annealing for 150-170 minutes, and then the temperature is further lowered to 10-30°C. After annealing, the lithium aluminum silicate ESP cover glass is obtained.

5. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 4, characterized in that: In step S1, before preheating, the glass is first cleaned with deionized water and then dried. The dried glass is wiped with alcohol gauze and then preheated again.

6. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 4, characterized in that: In step S1, the molten mixed molten salt includes the following components in mass percentage: KNO3 85-92%, NaNO3 4-9% and KCl 3-6%.

7. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 6, characterized in that: In step S1, the molten mixed molten salt includes the following components in mass percentage: KNO3 88%, NaNO38% and KCl 4%.

8. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 4, characterized in that: In step S2, the molten mixed molten salt includes the following components in mass percentage: KNO3 90-95%, KOH 1-4%, AgNO3 0.5-2.5%, CsNO3 0.5-2%, Al2O3 1-3%, and Na3PO4 0.5-1%.

9. The process for preparing the lithium aluminosilicate ESP cover glass according to claim 8, characterized in that: In step S2, the molten mixed molten salt includes the following components in mass percentage: KNO3 90%, KOH 4%, AgNO3 2.5%, CsNO3 1.5%, Al2O3 1.5%, and Na3PO4 0.5%.